Spatial variation in the willingness to accept payments for conservation of a migratory wildlife corridor in the Athi-Kaputiei Plains, Kenya - Leeuw, Jan de; Said, Mohammed Yahya; Kifugo, S.C.; Ogutu, Joseph O.; Osano, Philip M. (Elsevier, 2014)
To be effective in promoting the conservation of migratory wildlife, recipients of payment for ecosystem services (PES) must be willing to accept payment along the entire migratory corridor. This paper investigates spatial variation in willingness to accept (WTA) payments made by the Wildlife Conservation Lease Program in the Athi-Kaputiei plains of Kenya. The program, designed as an incentive to keep land open for wildlife and livestock, offers land owners 10 US$ per ha per year, irrespective of location. We model the relation between WTA and distances to roads, towns and rivers, annual precipitation and slope and display the predicted spatial variation in WTA. The results reveal significant spatial variation in willingness to accept payments for availing land for conservation, with higher WTA concentrated away from roads and also in the Southeast of the plains. The results further suggest that wildlife movement will be blocked due to low WTA in the proximity of towns and tarmacked roads. We conclude that an effective strategy to keep the land open for migratory wildlife should consider spatial variation in WTA payment for land lease. It is suggested to consider stratifying the lease rates geographically to reflect the underlying spatial variation in WTA.